Peningkatan Hasil Belajar Menulis Karangan Sederhana melalui Metode Picture and Picture pada Masa Covid 19 Siswa Kelas III Semeter Genap SDN 3 Masbagik Selatan Tahun Pelajaran 2020/2021 - Kustini, Kustini (TSAQOFAH, 2021)
The purpose of this study was to improve teacher skills, student activities and students' skills in writing simple essays for third grade students of SDN 3 Masbagik Selatan. The design of this research is classroom action research with stages of planning, implementation, observation and reflection. The research was carried out in 2 cycles, each cycle having 1 meeting. The research subjects were teachers and third grade students, totaling 15 students. Data collection techniques used tests, observations, field notes, and documentation. The results showed an increase in teacher skills. In the first cycle, the teacher got a score of 3.4 in the Active category and in the second cycle, the teacher got a score of 4.5 with the very active category. Student activity in the first cycle obtained an average score of 21.3 in the moderate category, and increased in the second cycle with an average score of 23.6 in the Active category. Students' skills in writing simple essays showed 53% classical completeness in the first cycle and increased to 100% in the second cycle. The conclusion of this study is that through picture and picture can improve teacher skills, student activities and student skills in writing simple essays. Suggestions for teachers should use innovative learning models and varied media.